Osteopontin is differentially expressed in renal cell tumors. (2nd April 2020) - Woźniak, Marta; Pawelak, Agnieszka; Makuch, Sebastian; Martuszewski, Adrian; Winograd, Kinga; Ziółkowski, Piotr; Agrawal, Siddarth
ABSTRACT: Osteopontin (OPN) has been shown to play a significant role in regulating the aggressiveness of cancer cells and promote tumor growth. Evaluation of this phosphorylated extracellular glycoprotein expression may help estimate its use as a potential prognostic marker in tumorigenesis of different renal tumors. The objective of the present study was to characterize for the first time the expression pattern of OPN in primary renal tumors and correlate its association to tumor progression and survival. A total of 68 primary renal tumors (clear cell renal cell carcinoma, oncocytoma, renal cell carcinoma, invasive urothelial carcinoma, papillary renal cell carcinoma, chromophobe renal cell carcinoma, papillary urothelial carcinoma) were analyzed by immunohistochemical staining and Western blot methods. Expression of OPN in relation to grading, histologic type of tumor, and survival was statistically assessed. Study data demonstrated that OPN is differentially expressed in various renal tumor cells types. It was shown that OPN is predominantly expressed at the protein level in clear cell renal cell carcinoma when compared to other types of renal tumors. In conclusion, osteopontin may be involved in the pathogenesis of renal tumors. However, the role of OPN expression in predicting the biological response requires further evaluation.